![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{49}+\sqrt{36}-\sqrt{25}+\sqrt{100}\)
\(=7+6-5+10\)
\(=18\)
có phải như vậy ko?
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\) \(A=\sqrt{49}-2\sqrt{36}+3\sqrt{4}\)
\(A=7-2.6+3.2\)
\(A=7-12+6\)
\(A=1\)
\(b)\) \(B=\frac{1}{2}\sqrt{\frac{144}{225}}-7\sqrt{100}+4\sqrt{\frac{361}{400}}\)
\(B=\frac{1}{2}.\frac{4}{5}-7.10+4.\frac{19}{20}\)
\(B=\frac{2}{5}-70+\frac{19}{5}\)
\(B=\frac{-329}{5}\)
Chúc bạn học tốt ~
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\sqrt{16}\cdot\sqrt{25}+\sqrt{196}:\sqrt{49}\)
\(=\sqrt{16\cdot25}+\sqrt{196:49}\)
\(=20+2=22\)
b) \(36:\sqrt{2\cdot3^2\cdot18}-\sqrt{169}\)
\(=36:\sqrt{324}-\sqrt{169}\)
\(=36:18-13=2-13=-11\)
c) \(\sqrt{\sqrt{81}}\)
\(=\sqrt{9}=3\)
d) \(\sqrt{3^2+4^2}\)
\(=\sqrt{9+16}=\sqrt{25}=5\)
a) \(\sqrt{16}.\sqrt{25}+\sqrt{196}\div\sqrt{49}\)
\(=4.5+14:7\)
\(=20+2=22\)
b) \(36:\sqrt{2.3^2.18}-\sqrt{169}\)
\(=36:18-13=-11\)
c) \(\sqrt{\sqrt{81}}=\sqrt{9}=3\)
d) \(\sqrt{3^2+4^2}=\sqrt{25}=5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
c) \(\frac{5}{8}+\frac{13}{10}-9+25=\frac{717}{40}\)
d) \(\sqrt{0,2^2}=\left|0,2\right|=0,2\)
e) \(\sqrt{\left(-0.3\right)^2}=0,3\)
g) \(-\sqrt{\left(-1.3\right)^2}=-1,3\)
h) \(-0,7\sqrt{\left(-0,7\right)^2}=-0,49\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a)
\(\sqrt{144}.\sqrt{\frac{49}{69}}\sqrt{0,01}=12.\frac{7}{\sqrt{69}}.0,1=\frac{8,4}{\sqrt{69}}=\frac{42\sqrt{69}}{345}\)
b)
\(\sqrt{0,25}-\sqrt{225}+\sqrt{2,25}=\sqrt{0,5^2}-\sqrt{15^2}+\sqrt{1,5^2}\)
\(=0,5-15+1,5=-13\)
c)
\(72:\sqrt{3^3+3^2}-3\sqrt{5^2-3^2}\)
\(=\frac{72}{\sqrt{36}}-3\sqrt{16}=\frac{72}{6}-3.4=12-12=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\sqrt{25}+2\sqrt{49}=5+2\cdot7=5+14=19\)
b) \(\sqrt{16}\cdot\sqrt{25}+\sqrt{169}:\sqrt{49}=4\cdot5+13:7=20+\dfrac{13}{7}\) = \(\dfrac{153}{7}\)
c) \(\sqrt{\left(3-\sqrt{7}\right)^2}+\sqrt{7}=3-\sqrt{7}+\sqrt{7}=3\)
d) \(2\sqrt{3}-\sqrt{75}+2\sqrt{12}=2\sqrt{3}-5\sqrt{3}+4\sqrt{3}\) \(=\sqrt{3}\)
\(\sqrt{36}.\sqrt{49}-\sqrt{225}:\sqrt{25}=6.7-15:5=39\)
\(=\sqrt{6^2}.\sqrt{9^2}-\sqrt{15^2}:\sqrt{5^2}=6.9-15:5=54-3=51\)=51